Analiza zależnego ryzyka ubezpieczeniowego - zastosowanie funkcji łączących - Heilpern, Stanisław (Analysis of Dependent Actuarial Risks - Application of Copulas, 2006)
The paper is devoted to the analysis of dependent actuarial risks based on the copulas. The strong assumption about independence of random variables is weaken in the investigated models. The dependence between some random variables is admitted. Such models are more realistic and they better describe the examined problems. The basic information connected with copulas, which are the main tools for study dependence, is presented in our paper. The Archimedean copulas, which induce the latent random variables treated as the influence of the common shock, are described. The distribution of the sum of dependent random variables is studied. The individual model of risk with dependent indicators is presented. This dependence is modeled by general and Archimedean copulas. The last part of our paper is devoted to the attempt of the application of copulas to the description of dependences in the multi-class collective risk model.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 269-285